Health Insurance Status and Disparities in Kidney Cancer Care. Issue 1 (January 2016) - Tan, Hung‐Jui; Chuang, Ryan J.; Shirk, Joseph D.; Laviana, Aaron A.; Hu, Jim C.
Abstract : Introduction: : Through PPACA (Patient Protection and Affordable Care Act) many adults have or will gain health insurance via Medicaid expansion. To understand how this policy change may potentially impact patients with kidney cancer we examined the relationship between insurance status and cancer related outcomes. Methods: : Using SEER (Surveillance, Epidemiology and End Results) data we identified 18, 632 patients 26 to 64 years old with kidney cancer from 2007 to 2009. For each patient we classified insurance status as no insurance, Medicaid or private insurance. After adjusting for patient and county characteristics we measured the association of insurance status with cancer stage, treatment and 1‐year mortality using multinomial logistic regression with clustering or generalized estimating equations as appropriate. Results: : In our study cohort 937 (5.0%) and 2, 027 patients (10.9%) had no insurance and Medicaid, respectively. These patients were more likely to be younger, nonwhite, unmarried and residing in areas with lower income, education or employment (p <0.001). On adjusted analyses uninsured and Medicaid patients more often presented with advanced disease (21.3% vs 19.6% vs 11.0%) but less frequently received treatment (86.2% vs 87.9% vs 93.4%, each p <0.001) compared with privately insured patients. These adults also died of kidney cancer more often (13.6% vs 12.5% vs 6.4%, p <0.001) likely due to differences in stage and receipt of cancer directed therapy. Conclusions: : Uninsured and Medicaid patients suffer disproportionately from kidney cancer with equal magnitude. Given the reliance on Medicaid, even as insurance coverage expands differences in outcomes will likely persist, underscoring the need for additional efforts that address disparities in kidney cancer care.